2021
DOI: 10.3389/fanim.2021.775311
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Stress in Chickens and the Potential Effectiveness of Dietary Vitamin Supplementation

Abstract: Environmental stressors can promote the vulnerability of animals to infections; it is therefore, essential to understand how stressors affect the immune system, the adaptive capacity of animals to respond, and effective techniques in managing stress. This review highlights scientific evidence regarding environmental stress challenge models and the potential effectiveness of vitamin supplementation. The major environmental stressors discussed are heat and cold stress, feed restriction, stocking density, and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 264 publications
(328 reference statements)
0
29
0
1
Order By: Relevance
“…Stress is a factor affecting the biology of the bird from both internal (homeostasis) and external factors (nutritional, environmental) affecting equilibrium and decreasing the production and reproduction performances [2]. Poultry suffer from various environmental stressors such as heat stress [3], cold stress [4], feed restriction [5], stocking density, pollutants, and many more [6].…”
Section: Introductionmentioning
confidence: 99%
“…Stress is a factor affecting the biology of the bird from both internal (homeostasis) and external factors (nutritional, environmental) affecting equilibrium and decreasing the production and reproduction performances [2]. Poultry suffer from various environmental stressors such as heat stress [3], cold stress [4], feed restriction [5], stocking density, pollutants, and many more [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they suggested an increase of dietary vitamin levels by 0.6 to 1.0% yearly is required to maintain constant vitamin intake per unit of output. Recently, it has been suggested that combination of multivitamins is more efficient than the use of individual vitamins ( Akinyemi and Adewole, 2021 ). In addition, dietary vitamins play an important role in poultry feed and could be used as an effective nutritional strategy for immunity and antioxidant modulation ( Shojadoost et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although environmental conditions alone do not directly cause illnesses in poultry, they weaken the general health and thus compromise immunity in birds, making them vulnerable to infections (Quarles & Kling, 1974; Butler & Egan, 1974; Reece & Lott, 1980; Sterling et al ., 2003; Kocaman et al ., 2006; Talukder et al ., 2010). In animals, stress under abnormal environmental conditions reduces humoral immune capacity and weakens cellular body defences (Bridle et al ., 2006; Dhabhar, 2014; Akinyemi & Adewole, 2021). By altering the Type 1–Type 2 cytokine equilibrium, long‐term stress reduces or causes imbalances in innate and adaptive immune responses, triggering low‐grade chronic inflammation and limiting numbers, movement and function of immunoprotective cells (Dhabhar, 2014).…”
Section: Introductionmentioning
confidence: 99%